2021
DOI: 10.21203/rs.3.rs-221595/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the Burden of Mental Distress Among Nurses at A Provincial COVID-19 Referral Hospital In Indonesia: A Cross-Sectional Study

Abstract: Background: The current outbreak of COVID-19 pandemic distorts not only the physical, but also mental and psychological condition of healthcare providers, especially the nurses who directly working with the COVID-19 patients. This study aims to investigate the prevalence and risk factors of depression, anxiety and stress among nurses working in a COVID-19 referral hospital in Indonesia. Methods: A cross-sectional study was conducted. A self-administered questionnaire, DASS21, along with the demographic questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The proportion of emotional mental disorders found in this study is similar to other previous findings: 18% of nurses in the United States experienced emotional mental disorders (Letvak et al., 2012), and 26.8% of nurses in Iran had depression (Fereidouni et al., 2018). The disorders found in this study were similar to those found in study conducted during the COVID‐19 pandemic (Iskandarsyah et al., 2021; Marthoenis et al., 2021; Sunjaya et al., 2021). However, the prevalences were skewed—much higher in hospitals providing care for patients with COVID‐19 and lower in non‐COVID‐19 healthcare facilities (Rochmawati et al., 2022; Sofiani et al., 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The proportion of emotional mental disorders found in this study is similar to other previous findings: 18% of nurses in the United States experienced emotional mental disorders (Letvak et al., 2012), and 26.8% of nurses in Iran had depression (Fereidouni et al., 2018). The disorders found in this study were similar to those found in study conducted during the COVID‐19 pandemic (Iskandarsyah et al., 2021; Marthoenis et al., 2021; Sunjaya et al., 2021). However, the prevalences were skewed—much higher in hospitals providing care for patients with COVID‐19 and lower in non‐COVID‐19 healthcare facilities (Rochmawati et al., 2022; Sofiani et al., 2021).…”
Section: Discussionsupporting
confidence: 89%
“…An Indonesian national survey showed that 50.9% of Indonesian nurses had experienced work stress, often feel dizzy, tired, less friendly and very tired (Pragholapati, 2020), and at a high risk of psychological distress (Prasanty et al., 2018). After the COVID‐19 outbreak, the risk of emotional mental disorders among nurses increased, and they have a higher risk for psychological trauma than other health professionals (Marthoenis et al., 2021; Sunjaya et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies in Indonesia (Marthoenis et al . 2021), Singapore (Chew et al . 2020), and Croatia (Salopek‐Ziha et al .…”
Section: Discussionmentioning
confidence: 99%
“…Following the discussion, this research work is intended to describe the lived experiences of COVID- 19…”
Section: The Problem or Research Questionmentioning
confidence: 99%